COVID-19 Pandemic, Air Quality, and PM2.5 Reduction-Induced Health Benefits: A Comparative Study for Three Significant Periods in Beijing - Cai, Fangfang; Yin, Kedong; Hao, Mengying (Frontiers in Ecology and Evolution, 2022)
The COVID-19 pandemic has developed as a severe public health hazard with far-reaching implications in all areas of the ecological environment. Numerous studies have been conducted on the effect of restriction efforts on air pollution throughout the world since the COVID-19 outbreak, but few have made a comparative study of several different periods and estimated the health benefits of PM2.5 decrease caused by the COVID-19 epidemic. Here, based on the observation data of air quality index (AQI) and five pollutants in three significant periods in China which are the initial outbreak of COVID-19, the epidemic outbreak in Beijing’s Xinfadi market, and the policy period of staying put during the Spring Festival in 2021, we established the least squares dummy variable model and difference-in-differences model respectively to evaluate the control measures impact on air pollutants of 16 urban areas in Beijing and carried on the comparative study to three different periods. We discovered that restriction measures did have an apparent impact on most air pollutants, but there were discrepancies in the three periods. The AQI fell by 7.8%, SO2, NO2, PM10, PM2.5, and CO concentration were lowered by 37.32%, 46.76%, 53.22%, 34.07%, and 19.97% respectively in the first period, while O3 increased by 36.27%. In addition, the air pollutants concentrations in the ecological environment, including O3, reduced significantly, of which O3 decreased by 7.26% in the second period. Furthermore, AQI and O3 concentration increased slightly in comparison to the same period in 2019, while other pollutants dropped with NO2 being the most obvious decrease in the third period. Lastly, we employed health effects and environmental value assessment methods to evaluate the additional public health benefits of PM2.5 reduction owing to the restriction measures in three periods. Generally speaking, this research not only provides a natural experimental basis for governance actions of air pollution in the ecological environment, but also points out a significant direction for future control strategies.